Origins And Development Of Forensic Medicine And Forensic Science In England, 1823-1946 - Ward, Jennifer (1993)
This study traces the development of forensic medicine, forensic science and police science from their roots in nineteenth-century England and shows that the main factors which make up the present-day disciplines were in place well before the First World War. The elite practice of forensic medicine had evolved into the laboratory-based sciences of special pathology and Home Office toxicological analysis by the 1900s and it is shown that in creating forensic science in the 1930s on this elite medical model as an aid to police investigations, other science and medicine in court, particularly in the civil courts, were excluded from the meaning of the new term 'forensic science' and perhaps also from the far older and wider 'forensic medicine'. There is confusion in the public mind as to the difference between forensic medicine and forensic science, or whether one is included in the other. By outlining the history of the separate specialities the meanings of the terms is clarified, not only for the present day, but at each earlier stage. Forensic medicine's role working for the state in criminal cases has always been badly funded, as the discipline has been unable to compete for public funds against more pressing needs. poor teaching and little or no original research. The creation of the Forensic Science Service was an attempt in part to salvage forensic medicine and to put it finally on an institutionalised footing, but this failed, and as the period of review closed in 1946 forensic medicine was still struggling for survival. Forensic science too looked set for failure as the government had made no provision for research or for training the new 'forensic scientists'